Peningkatan Hasil Belajar Siswa Menggunakan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Modul dan Jobsheet Instalasi Motor Listrik pada Siswa Kelas XI-B TITL di SMK Negeri 3 Metro Tahun Pelajaran 2018/2019 - Rudianto Sitohang (eductum: Jurnal Literasi Pendidikan, 2022)
This study aims to improve student learning outcomes in class XI TITL B in the subject of Electrical Motor Installation using the Problem Based Learning (PBL) learning model at SMK Negeri 3 Metro. This research is a Classroom Action Research with the model developed by Kemmis and Mc Taggart. The subjects of this study were 34 students of class XI TITL B in the even semester of the 2018/2019 academic year. This study consisted of two cycles with each cycle consisting of two meetings. Data collection techniques in this study used observation sheets, learning outcomes tests, and documentation. The data analysis technique used is descriptive analysis. The criteria for success in this study is that at least 75% of student learning outcomes have achieved completeness (KKM= 70). The results showed that the implementation of learning using the PBL learning model could improve the learning outcomes of class XI students in the subject of Electrical Motor Installation. This can be seen from the increase in student learning outcomes which are measured using pretest and posttest in each cycle. The percentage of completeness in the pretest cycle I showed 14.71%, then in the posttest cycle I became 55.88% an increase of 41.17%. In the second cycle pretest showed 44.12%, then in the second cycle posttest to 82.35% an increase of 38.23%. The increase in the percentage of completeness posttest I and posttest II increased by 26.47%. The conclusion of this study is that student learning outcomes increase after using the PBL model.